"I Am Not on the Footing of Kept Women": Extra-Marital Love in Eighteenth-Century England. (26th May 2020) - Gibson, Kate
ABSTRACT: This article uses the letters of one woman, 'E.B.', to indicate the experience of a woman engaged in an extra-marital sexual relationship in eighteenth-century England. Most existing studies of extra-marital relationships emphasise exploitation, social ostracism and economic precariousness. This article argues in contrast that women could manipulate mainstream discourses of romantic love in order to construct a positive self-identity and negotiate the association of extra-marital sex with shame. Women were not excluded from debates over the individualistic pursuit of happiness that characterised an eighteenth-century 'sexual revolution', but were able to re-appropriate discourses of sexual freedom and sensibility in defence of extra-marital relationships.